1986
DOI: 10.1002/hed.2890090207
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the accessory nerve and its cervical contributions in the neck

Abstract: Details of the course of the accessory nerve and the pattern of the cervical contributions to the nerve are essential for planning neck dissection. Based on a recent anatomic description, a technique was devised to preserve the distal accessory nerve; the theory advanced was that the trapezius was supplied by motor fibers from the cervical plexus, which join the accessory nerve in the posterior triangle. Dissections were performed on 23 cadavers to test such a theory. The course of the accessory nerve in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 6 publications
(3 reference statements)
4
88
2
Order By: Relevance
“…In a recent study, this communication was found in 22 neck dissections (11 cadavers) and most of them were observed at the inferior border of submandibular gland (Domet et al, 2005). Communications between the cervical plexus and spinal accessory nerve are also well known and have been reported in the past (Soo et al, 1986;Kierner et al, 2000). Branches of cervical plexus rarely communicate with phrenic nerve (Loukas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, this communication was found in 22 neck dissections (11 cadavers) and most of them were observed at the inferior border of submandibular gland (Domet et al, 2005). Communications between the cervical plexus and spinal accessory nerve are also well known and have been reported in the past (Soo et al, 1986;Kierner et al, 2000). Branches of cervical plexus rarely communicate with phrenic nerve (Loukas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Contributions from cervical nerve 2-4 also may provide additional protection against extrinsic damage. 21 Some authors have speculated about other mechanisms, such as direct nerve damage and vascular sclerosis, but their role in radiation cranial nerve palsy awaits further study.…”
Section: Discussionmentioning
confidence: 99%
“…In all the reported cases, SAN received these contributions deep in the SM [8,9]. For the first time, we are reporting the presence of communicating branch in the posterior triangle.…”
Section: Introductionmentioning
confidence: 74%
“…Most of these contributions come from the C2, both C2 and C3, or C3 spinal nerves [8]. In a study, Lee et al, [9] found the contributions from C2 in 53.1% cases; from C2 and C3 in 38.1% cases and anatomy Section…”
Section: Discussionmentioning
confidence: 97%